Acute Corneal Transplant Rejection After Severe Acute Respiratory Syndrome Coronavirus 2 mRNA-1273 Vaccination. Issue 2 (22nd October 2021) - Yu, Suyeon; Ritterband, David C.; Mehta, Isha
Abstract : Purpose: The purpose of this article was to report a case of full-thickness corneal transplant rejection 3 days after immunization with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Moderna mRNA-1273 vaccine. Methods: Case Report. Results: A 51-year-old man with a history of keratoconus and penetrating keratoplasty underwent repeat penetrating keratoplasty for graft failure. The patient had an uncomplicated intraoperative and postoperative course with improved vision and a healthy graft. The patient received the SARS-CoV-2 Moderna vaccine on postoperative week 3, and within 3 days, the patient began developing eye pain, photophobia, and blurred vision. The patient was found to have graft rejection with corneal edema and endothelial keratic precipitates. The rejection did not improve despite a trial of increased topical steroids and ultimately evolved into graft failure. Conclusions: To the best of our knowledge, this case of full-thickness graft rejection after the Moderna SARS-CoV-2 mRNA vaccination is the first to be reported worldwide. The temporal relationship between vaccination and subsequent rejection is highly suggestive of causation due to the short interval (3 days) between vaccination and rejection and the lack of other inciting factors in an otherwise healthy graft. Patients with corneal transplants who plan to take the COVID-19 vaccinations should be counseled on symptoms and closely monitored, and an individualized plan should be made in discussion with the ophthalmologist.